Estudo do potencial anticâncer de um derivado de Chalcona, 1-(4-Nitrofenil)-3-Fenilprop-2-En-1-Ona, in vitro e in vivo - Mousinho, Kristiana Cerqueira (2010)
The substance 1- (4-Nitrofenil)-3- fenilprop-2- en-1-ona (CG) is a chalcone derivative, synthesized from a chemical reaction between acetophenone and p-nitro benzaldehyde. To evaluate its anticancer potential a pharmacological study of its antitumor properties in selected biological models in vitro e in vivo. CG presented a powerful cytotoxic activity in the 5 tested tumor lines evaluated, inhibiting cell proliferation of the tumor lines in the MTT assay and human peripheral mononuclear blood cells (PMBC) through the Alamar Blue assay. All cell lines showed sensitivity to the treatment with the CG, and the IC50 varied from 1,18 µM in HCT-8 to 3,32 µM in SF-295. The sample presented weak cytotoxic effect (IC50 of 7,07 µM) in cells PMBC, with 72h exposure to CG, compared to HL-60 cells (leukemic cell line), used in the next biological tests. The sample was incubated with the cells during 24h for the majority of the experiments. Additionally, CG did not induce hemolytic effects. The Tripan Blue assay showed a decrease of the cellular viability especially after 24h of incubation of the higher tested concentration (4 µM) with 58,4%. In assays for antiproliferative activity, OA/BE showed in its morphology cells going under apoptosis in the two higher concentrations, whereas the BrdU assay, presented incorporation of the same in the tested concentrations. The morphology analyzed with the May-Grunwald-Giemsa stain showed a decrease of the cellular volume, chromatin condensation and nuclear fragmentation.CG induced apoptosis in HL-60 cells, with participation of the intrinsic pathway and major stimulation of the extrinsic pathway, in a concentration-dependent manner, as observed in the cytoplasmatic membrane integrity, increase of DNA fragmentation and outsourcing of phosphatidylserine. In the cellular cycle analysis, it was observed a stop in the G2/M phase, activating caspases 3, 7, 8 and 9 (the last one in the highest concentration and confirmed by the Western blot assay). It was not observed activation of Cytochrome c. CG was not capable to induce mutagenic/genotoxic processes (comet assay and micronucleus in vitro). In the in vivo antitumor activity assay, tumor inhibition was observed in the tested doses (25 and 50mg/Kg/day, oral intake) of 54,85 and 69,11%, respectively . The doses of CG caused cellular swelling and the arise of inflammatory focus in the parenchyma or hepatic/renal stroma, focal nephrotoxic necrosis, microvesicular steatosis, hemosiderin pigments, hyperplasia of Kupffer cells, congestion of the red pulp and disorganization of the splenic lymphoid follicles. Furthermore, the biochemical indices had shown increase of AST and reduction of urea (25mg/Kg/day of CG), reduction of ALT (25mg/Kg/day of 5-FU and CG); hematologic alterations showed leukopenia and thrombocytopenia (5-FU), increase of total leukocytes (50mg/Kg/day of CG), increase of neutrophils and lymphocytes in all treated groups. All results led us to emphasize that CG possesses great potential as a promising molecule for its anticancer properties.